Black Esophagus: A Rare Case of Acute Esophageal Necrosis Induced by Diabetic Ketoacidosis in a Young Adult Female - Zachary Field; Jacqueline Kropf; Meghan Lytle; Giselle Castaneira; Mario Madruga; S. J. Carlan (Case Reports in Gastrointestinal Medicine, 2018)
Background. Acute esophageal necrosis is an uncommon clinical disorder diagnosed on endoscopy as a black esophagus. It has a multifactorial etiology that probably represents a combination of poor nutritional status, gastric outlet obstruction, and ischemia secondary to hypoperfusion of the distal esophagus. It typically occurs in older males with comorbidities. Case. A 37-year-old woman presented with diabetic ketoacidosis and hematemesis. At esophagogastroduodenoscopy acute esophageal necrosis was diagnosed. The treatment included fluid and electrolyte management, insulin, and a proton pump inhibitor. She improved and left the hospital on day 3. Conclusion. Diabetic ketoacidosis can result in a profound osmotic diuresis, fluid loss, and hypoperfusion of the distal esophagus. This condition can then lead to ischemic injury and acute esophageal necrosis. Awareness of the possibility of its presence in young women with hematemesis and poorly controlled diabetes is important since early identification with esophagogastroduodenoscopy is necessary to prevent serious postnecrotic complications.